Multimodal treatment of unresectable hepatocellular carcinoma to achieve complete response results in improved survival. Issue 5 (12th January 2015) - Newell, Pippa H.; Wu, YingXing; Hoen, Helena; Uppal, Richa; Thiesing, John Tyler; Sasadeusz, Kevin; Cassera, Maria A.; Wolf, Ronald F.; Hansen, Paul; Hammill, Chet W
Abstract Introduction With technological advances, questions arise regarding how to best fit newer treatment modalities, such as transarterial therapies, into the treatment algorithm for patients with hepatocellular carcinoma (HCC). Methods Between 2005 and 2011, 128 patients initially treated with transarterial radioembolization or chemoembolization using drug‐eluting beads were identified. The response was graded retrospectively. Toxicity was measured 1, 3, and 6 months after the first and last treatments. Results Sixty‐five patients (53%) were advanced stage. Twenty patients (16%) had an initial complete response, but with additional treatments, this was increased to 46 (36%). Patients with a complete response as their best response to treatment had a median survival [95% confidence interval (CI)] of 5.77 (2.58, upper limit not yet reached) years, significantly longer than those whose best response was a partial response, 1.22 (0.84, 2.06) years and those with stable disease as their best response, 0.34 (0.29, 0.67) years. Repeated treatments did not increase toxicity. Discussion This retrospective review of patients treated for intermediate and advanced stage HCC revealed a significant survival advantage in patients who achieved a complete response. These data support use of a multi‐modality approach to intermediate and advanced stage HCC, combining liver‐directed treatments as necessary to achieve a complete response.